NEW BACTERIOLYTIC ENZYME PREPARATION N-ACETYL-D-GLUCOSAMINIDASE - Rozhkova, A.M.; Chulkin, A.M.; Sinelnikov, I.G.; Sinitsyna , O.A.; Zorov , I.N.; Sinitsyn, A.P. (Eurasian Journal of Applied Biotechnology, 2024)
A new nag1 gene encoding N-acetyl-D-glucosaminidase from Streptomyces kursanovii was cloned. The soluble form of N-acetyl-D-glucosaminidase was obtained after improving its expression in E. coli ArcticExpressTM (DE3) cells. The homogeneous form of the enzyme was isolated by affinity chromatography, and its bacteriolytic ability against cells of the Gram-positive bacterium Micrococcus lysodeikticus was studied. It was demonstrated that the new enzyme’s bacteriolytic capacity surpasses that of chicken lysozyme.